Determination of additional canals in maxillary first permanent molars in adult Nigerian population: Using in vivo and in vitro techniques - Oboro-Onuora, Helen O.; Onuora, Obiajulu I.; Sede, Mathew A. (European Journal of General Dentistry, 2012)
Objective: To determine the prevalence of additional canals in maxillary first permanent molar in an adult population in Nigeria. Materials and Methods: This was a cross sectional study done using both in vivo and in vitro techniques. A total of 156 teeth were used; 50 for the in vivo and 106 for the in vitro study. Dental loupes and gentle troughing of the pulpal floor was done, to look for additional canal in the in vivo study, while the teeth in vitro study were sectioned at three levels after impregnation with a dye and magnifying glass was used to look for additional canals. Results: In the in vivo aspect of the study a total of 50 patients were treated, of this number 17 (34.0%) had additional canals, these were all found in the mesiobuccal roots. In the in vitro phase of the study 106 teeth were examined, sectioning at the cementoenamel junction revealed that 6 (5.7%) and 2 (1.9%) of the mesiobuccal and palatal roots had additional canals. Sectioning at the furcation and middle of the mesiobuccal, distobuccal and palatal roots revealed that 76 (71.1%) and 80 (75.5%) of the mesiobuccal roots respectively had additional canals. Conclusion: It can be concluded, from the clinical, as well as the laboratory aspect of this study that the incidence of additional canals in the maxillary first permanent molar, in this environment, is much higher than what was previously reported, and when these additional canals are present, they are usually found in the mesiobuccal root.
Keywords: Additional canal; maxillary first permanent molar; microscopy; Nigerian; troughing